2016
DOI: 10.3892/ol.2016.4190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synchronous solitary bone metastasectomy and lung cancer resection on non-small cell lung cancer patients

Abstract: Abstract. Lung cancer is the most frequent cause of cancer-associated mortality among men and women globally. The skeleton is one of the most common metastatic sites. The majority of patients exhibiting bone metastases are treated using systemic therapy or symptom-based palliative approaches without surgery. The present study attempted to improve the therapeutic effects of synchronous surgeries in resectable non-small cell lung cancer patients exhibiting solitary bone metastasis. A total of 5 patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
10
1
Order By: Relevance
“…Aggressive treatment for patients with oligometastatic stage IV lung cancer has been shown to be associated with a favorable outcome. [22][23][24][25][26][27] However, our data cannot confirm the role of a radical treatment approach for the metastatic lesion in the M1b group. This could be due to the heterogeneity of metastatic organs in the M1b group and low statistical power owing to the small sample size.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Aggressive treatment for patients with oligometastatic stage IV lung cancer has been shown to be associated with a favorable outcome. [22][23][24][25][26][27] However, our data cannot confirm the role of a radical treatment approach for the metastatic lesion in the M1b group. This could be due to the heterogeneity of metastatic organs in the M1b group and low statistical power owing to the small sample size.…”
Section: Discussionmentioning
confidence: 82%
“…This could be due to the heterogeneity of metastatic organs in the M1b group and low statistical power owing to the small sample size. As previous reports regarding this issue were also based on a small number of cases and retrospectively analyzed data, 22,24,26,27 a well-organized prospective trial is necessary to draw a reliable conclusion for this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of surgical resection, adjuvant radiochemotherapy, immunotherapy and individualized targeted therapy have improved in recent years; however, the 5-year survival rate of NSCLC patients remains ~15% (3). The occurrence and development of lung cancer is closely associated with the biological behavior of lung cancer cells, although the molecular mechanism that drives the disease remains unclear (4)(5)(6). It is widely accepted that the proliferation, invasion and metastasis of tumor cells, and the alteration of intrinsic cellular processes such as apoptosis and the cell cycle, promotes the occurrence and development of NSCLC (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In another case series by Zhao et al, five patients underwent synchronous lung cancer resections and solitary bone metastasectomies, the progression-free survive of the patients was 13.2 ± 7.7 months [57]. Zhao et al concluded lung tumor resection with bone metastasectomy is a safe method in selected cases [57].…”
Section: The Management Of Skeletal System Oligometastasis Of Nsclcmentioning
confidence: 99%
“…In another report by Hirano et al, two NSCLC cases had bone oligometastasis in the fibula and femur, surgical excision was performed both for the primary tumor site and bone metastasis, and the patients were still alive for more than five years [55]. In another case series by Zhao et al, five patients underwent synchronous lung cancer resections and solitary bone metastasectomies, the progression-free survive of the patients was 13.2 ± 7.7 months [57]. Zhao et al concluded lung tumor resection with bone metastasectomy is a safe method in selected cases [57].…”
Section: The Management Of Skeletal System Oligometastasis Of Nsclcmentioning
confidence: 99%